Analysis Of Harmonic Source Identifier Using Periodogram - Mat Kassim, Nabilah; Abdullah, Abdul Rahim; Abdul Kadir, Aida Fazliana; Shamsudin, Nur Hazahsha (Asian Research Publishing Network (ARPN), 2016)
-